Initial experience of abdominal total mesorectal excision for rectal cancer using the da Vinci single port system - Wed Alshalawi; Chul Seung Lee; In Kyeong Kim; Yoon Suk Lee (Journal of Minimally Invasive Surgery)
From November 2021 to February 2022, 15 patients underwent total abdominal mesorectal excision for rectal cancer using the da Vinci single port system. The clinical and pathological results were analyzed retrospectively. All surgeries were performed without conversion. The mean distance from the tumor to the anal verge was 10 cm (range, 2-15 cm). The mean operative time was 191 minutes, the median docking time was 4 minutes (range, 2-10 minutes), and the estimated blood loss was 20 mL (range, 20-50 mL). The mean number of lymph nodes harvested was 16.5, the mean distal resection margin was 3.52 cm, and all patients had circumferential and distal tumor-free resection margins. One patient had minor anastomotic leakage. The mean length of hospital stay was 5.8 ± 2.5 days. Abdominal total mesorectal excision using the da Vinci single port system for rectal cancer is technically feasible and safe, with acceptable pathological and short-term clinical outcomes.